Kepatuhan wajib pajak orang pribadi: Studi aspek pengetahuan, kesadaran, kualitas layanan dan kebijakan sunset policy - Suyanto Suyanto; Yhoga Heru Pratama (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
This research aims to test the effects of taxpayers’ knowledge and awareness, tax officials’ service quality, and the sunset policy on individual taxpayers’ compliance. The study focuses on individual taxpayers who run their business activities in Jogjakarta City to investigate: (1) the effect of taxpayers’ knowledge on taxpayers’ compliance, (2) the effect of taxpayers’ awareness on taxpayers’ compliance, (3) the effect of tax officials’ service quality on taxpayers’ compliance, (4) the effect of the sunset policy on taxpayers’ compliance. The study generates the primary data by distributing the questionnaires to individual taxpayers in Jogjakarta City as the respondents. Using the accidental sampling method, the data collection generates 108 respondents, with 77 usable responses. The multiple regression analysis shows that (1) taxpayers’ knowledge does not affect their tax compliance, (2) taxpayers’ awareness exhibit a positive effect on taxpayers’ compliance, (3) tax officials’ service quality does not affect taxpayers’ compliance, and (4) the sunset policy does not affect taxpayers’ compliance.